Implementation of Multi-host Podcast-Based Learning Videos in Multimedia Concept Courses - Feggie Violency Tarigan (Politeknik Negeri Batam, 2022)
Learning through digital means is a modern method of education that has been influenced by rapid development of communication technology and information in the era of industrial revolution 4.0. In universities, teaching and learning activities have been changed because of the COVID-19 pandemic. Multihost podcasts based on learning videos have emerged as an alternative learning media for online study in Multimedia Concept programs. Based on the results of distributing a questionnaire, the research method used has been a 4D Model with the conclusion that multihost podcast-based learning videos are highly feasible with a percentage rate of 86,8% from the perspective of video display, learning content and understanding. As an effective and efficient learning medium, podcasts have substantial potential for university students.